Chronic Caloric Restriction and Exercise Improve Metabolic Conditions of Dietary-Induced Obese Mice in Autophagy Correlated Manner without Involving AMPK - Mingxia Cui; Han Yu; Jinli Wang; Junjie Gao; Ji Li (Journal of Diabetes Research)
Aim. To investigate the role of AMPK activation and autophagy in mediating the beneficial effects of exercise and caloric restriction in obesity. Methods. Dietary-induced obesity mice were made and divided into 5 groups; one additional group of normal mice serves as control. Mice in each group received different combinations of interventions including low fat diet, caloric restriction, and exercise. Then their metabolic conditions were assessed by measuring serum glucose and insulin, serum lipids, and liver function. AMPK phosphorylation and autophagy activity were detected by western blotting. Results. Obese mice models were successfully induced by high fat diet. Caloric restriction consistently improved the metabolic conditions of the obese mice, and the effects are more prominent than the mice that received only exercise. Also, caloric restriction, exercise, and low fat diet showed a synergistic effect in the improvement of metabolic conditions. Western blotting results showed that this improvement was not related with the activation of AMPK in liver, skeletal muscle, or heart but correlates well with the autophagy activity. Conclusion. Caloric restriction has more prominent beneficial effects than exercise in dietary-induced obese mice. These effects are correlated with the autophagy activity and may be independent of AMPK activation.